Magnetohydrodynamics in Presence of Electric and Magnetic charges - Bisht, Praveen Singh; Pushpa, . .; Negi, O. P. S. (Communications in Physics, 2012)
Starting from the generalized electromagnetic field equations of dyons, the magnetohydrodynamics (MHD) of plasma for particles carrying simultaneously the electric and magnetic charges (namely dyons), has been reformulated in terms of the electromagnetic duality. Consequently, the frequency of dyonic plasma is obtained for real value of wave number \(k\). In this case, only those generalized electromagnetic waves are allowed to pass, for which the usual frequency is greater than the plasma frequency (i.e. \(ω>ω_p)\). Accordingly, the Ohm’s law has been re-described to derive the plasma oscillation equation, Magnetohydrodynamic wave equation and to calculate the energy of dyons in unique and consistent manner.